Exploring Anthropological Approaches to Public Policy in Nepal: A Post-Qualitative Inquiry - Pun, Lal Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2025)
By and large, public policy is understood as an administrative construct, comprising institutional mechanisms, economic priorities, and political choices. In the spaces where it is duly enacted, policies face challenges and are reshaped by the sociocultural rhythms at large. In Nepal, policy research basically focuses on statistics, procedures, and formal rules, often neglecting the lived experiences of local people and their indigenous knowledge. Recognizing these processes revealed deep entanglement with people’s experiences and cultural performances, echoing the relational knowledge of the policy researcher and the people being studied. Drawing on this excerpt, I employ anthropological approaches in Nepal and reimagine sociocultural constructs that shape policy. This study is guided by post-qualitative inquiry; my engagements with policymakers, anthropologists, public policy experts, and practitioners unfolded conversations in homes, teahouses, and cafés, where knowledge is co-constructed with my research companions. Employing Anthony Giddens’ (1986) Structuration Theory, I explored how structures or systems and human actions constantly shape and reshape one another in everyday life. In Nepal’s policy landscape, anthropology is sidelined, as technocratic approaches, bureaucratic frameworks, and rigid institutional mechanisms largely limit policies. These constraints are never absolute. Individual actors, including policymakers, scholars, public policy experts, and advocates, continue to introduce culturally sensitive and context-aware approaches into policy spaces. Anthropology thus becomes visible not only in policy documents but also in how policies are lived, interpreted, and negotiated across different contexts, as these entanglements imply that policy knowledge is largely relational, embodied, and evolving, not static. Anthropological insights not only complement policy research but also reshape how policy is enacted, making it more inclusive, culturally grounded to address people’s pressing issues, and responsive to policy ecosystems in Nepal.